Sulfanilic Acid Pending on a Graphene Scaffold: Novel, Efficient Synthesis and Much Enhanced Polymer Solar Cell Efficiency and Stability Using It as a Hole Extraction Layer - Zhao, Fu-Gang; Hu, Cheng-Min; Kong, Yu-Ting; Pan, Bingyige; Yao, Xiang; Chu, Jian; Xu, Zi-Wen; Zuo, Biao; Li, Wei-Shi (ACS applied materials & interfaces, 2018)
In this contribution, we describe a novel, facile, and scalable methodology for high degree functionalization toward graphene by the reaction between bulk graphite fluoride and in situ generated amine anion. Using this, the rationally designed sulfanilic acid pending on a graphene scaffold (G-SO3H), a two-dimensional (2D) π-conjugated counterpart of poly(styrenesulfonate), is available. Combined reliable characterizations demonstrate that a very large quantity of sulfanilic blocks are linked to graphene through the foreseen substitution of carbon–fluorine units and an unexpected reductive defluorination simultaneously proceeds during the one-step reaction, endowing the resultant G-SO3H with splendid dispersity in various solvents and film-forming property via the former, and with recovered 2D π-conjugation via the latter. Besides, the work function of G-SO3H lies at −4.8 eV, well matched with the P3HT donor. Awarded with these fantastic merits, G-SO3H behaves capable in hole collection and transport, indicated by the enhanced device efficiency and stability of polymer solar cells (PSCs) based on intensively studied P3HT:PCBM blends as an active layer. In particular, comparison with conventional poly(3,4-ethylenedioxythiophene) doped with poly(styrenesulfonate) and recently rising and shining graphene oxide, G-SO3H outperforms above 17 and 24%, respectively, in efficiency. More impressively, when these three unencapsulated devices are placed in a N2-filled glovebox at around 25 °C for 7 weeks, or subject to thermal treatment at 150 °C for 6 h also in N2 atmosphere, or even rudely exposed to indoor air, G-SO3H-based PSCs exhibit the best stability. These findings enable G-SO3H to be a strongly competitive alternative of the existing hole extraction materials for PSC real-life applications.